2012
DOI: 10.1371/journal.pntd.0001854
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq Analysis of the Parasitic Nematode Strongyloides stercoralis Reveals Divergent Regulation of Canonical Dauer Pathways

Abstract: The infectious form of many parasitic nematodes, which afflict over one billion people globally, is a developmentally arrested third-stage larva (L3i). The parasitic nematode Strongyloides stercoralis differs from other nematode species that infect humans, in that its life cycle includes both parasitic and free-living forms, which can be leveraged to investigate the mechanisms of L3i arrest and activation. The free-living nematode Caenorhabditis elegans has a similar developmentally arrested larval form, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
191
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(202 citation statements)
references
References 142 publications
(245 reference statements)
10
191
1
Order By: Relevance
“…Hc-daf-2 transcripts are present throughout the entire life cycle, but are significantly upregulated in the iL3 stage. This upregulation might relate directly to developmental arrest, in preparation for further reproductive development, and is consistent with the transcription profiles for Ss-daf-2b , Ss-age-1 , Ss-pdk-1 and Ss-akt-1 in S. stercoralis (see Stoltzfus et al, 2012b; Massey et al, 2013). This information indicates that the insulin-like receptor encoded by Hc-daf-2 plays a crucial role in the transition from a developmentally arrested to an activated state in H. contortus .…”
Section: Discussionsupporting
confidence: 83%
“…Hc-daf-2 transcripts are present throughout the entire life cycle, but are significantly upregulated in the iL3 stage. This upregulation might relate directly to developmental arrest, in preparation for further reproductive development, and is consistent with the transcription profiles for Ss-daf-2b , Ss-age-1 , Ss-pdk-1 and Ss-akt-1 in S. stercoralis (see Stoltzfus et al, 2012b; Massey et al, 2013). This information indicates that the insulin-like receptor encoded by Hc-daf-2 plays a crucial role in the transition from a developmentally arrested to an activated state in H. contortus .…”
Section: Discussionsupporting
confidence: 83%
“…102 Polyadenylated transcriptome analysis of S. stercoralis and comparison with dauer stage C. elegans revealed that in both S. stercoralis and C. elegans, the genes encoding Cyclic Guanosine Monophosphate (cGMP) pathway components were coordinately upregulated in L3i, suggesting that dauer pathway genes are present in S. stercoralis and may play a role in L3i development. 103 Microarray analysis of L3i and L1 of S. stercoralis helped to identify 935 differentially expressed genes between these two stages, 104 and similar results were reported using S. ratti transcriptome. 100 Overall, using Strongyloides EST representation and microarray data, there was rather little evidence for the conservation of transcriptional profiles between S. ratti and S. stercoralis or C. elegans.…”
mentioning
confidence: 57%
“…The S. stercoralis (PV001 line), derived from a single female worm of the UPD strain, was maintained as described previously [24,[34][35][36][37]. Transcription profiles of Ss-riok-3 were assessed in seven developmental stages of the PV001 line of S. stercoralis, including free-living females (FL Female), post-free-living first-stage larvae (PFL L1), infective third-stage larvae (iL3), in vivo activated third-stage larvae (L3+), parasitic females (P Female), post-parasitic first-stage larvae (PP L1) and post-parasitic third-stage larvae (PP L3).…”
Section: Transcriptional Analysismentioning
confidence: 99%
“…The parasites from different stages were isolated as described previously [34,35]. Transcription was quantified using RNA-seq [35]. Raw RNA-seq data for the seven developmental stages are available at http://www.…”
Section: Transcriptional Analysismentioning
confidence: 99%
See 1 more Smart Citation